Hello ladies and gents,

Ive got an exercise in which I have to fully parenthesize expressions using the higher-lower precedence, for instance:

a+b*c would become (a+(b*c)) because multiplication has a higher precedence then addition.

Here are my solutions for the following expressions:

1) a = b + c * d << 2 & 8

(a = ((b + (c * d)) << 2 & 8))

2) a & 077 != 3

Don't think there is a solution for this since & is "adress of", but how can you have an adress of 077?

3) a == b || a == c && c < 5

(((a == b) || ((a == c) && (c < 5))))

4) c = x != 0

(c = (x != 0))

5) 0 <= i < 7

((0 <= i) < 7)

6) f(1, 2) + 3

((f(1, 2)) + 3)

7) a = - 1 + + b -- - 5

Don't think there is a solution either since the expressions are not correct?

8) a = b == c ++

(a = (b == (c ++)))

9) a = b = c = 0

(a = (b = (c = 0)))

10) a[4][2] *= * b ? c : * d * 2

((a[4][2]) *= (* b ? c : ((* d) * 2)))

11) a-b, c=d

((a-b), (c=d))

I was hoping that you guys could check these out and tell me which ones are wrong?

Thank you.